Determinants of Non-Performing Loans: Evidence from Malaysia - Mohd Amil, Che Wan Nabilah Che W; Haris, Balkis; Kassim, Nor Akila Mohd (Information Management and Business Review, 2023)
Financial institutions worldwide have huge dangers in non-performing loans. Hence, they are required to review their lending policies. The default loans also lead to massive losses on banks and decreased economic growth. Therefore, non-performing loans are a predominant concern that affects financial markets and banking industry suitability. The rise in non-performing loans has an adverse impact on the banking sector. Therefore, understanding the determinants of non-performing loans is critical to safeguard the overall economy’s productivity. Motivated by this scenario, this study investigates the determinants of Non-Performing Loans in Malaysia’s banking system. Inflation Rates, Lending Interest Rates, Real Interest Rates, Gross Domestic Product, Gross Domestic Saving and Unemployment Rates are the variables used and collected yearly from 1988 to 2020, consisting of 33 observations for each variable. The method used for data analysis in this study is multiple regression analysis. The research results revealed that Gross Domestic Product, Gross Domestic Saving, and Unemployment significantly explained Non-Performing Loans in Malaysia. The findings have important implications for policymaking, besides adding new knowledge to the existing literature.